Numerical simulation of fracture characteristics of jointed rock masses under blasting load. Issue 6 (8th July 2019) - Liu, Chao; Yang, Mingyang; Han, Haoyu; Yue, Wenping
Abstract : Purpose: To study fracture characteristics of jointed rock masses under blasting load, the RFPA2D analysis software for dynamic fracture of rocks based on the finite element method and statistical damage theory was used. Design/methodology/approach: On this basis, this research simulated the fracture process of rock masses in blasting with different joint geometrical characteristics and mainly analysed the influences of distance from joints to blasting holes, the length of joints, the number of joints and joint angle on fracture of rock masses. Findings: The calculation results show that with the constant increase of the distance from joints to blasting holes, the influences of joints on blasting effects of rock masses gradually reduced. Rock masses with long joints experienced more serious damages than those with short joints. Damages obviously increased with the changing from rock masses without joints to rock masses with joints, and when there were three joints, the further increase of the number of joints had unobvious changes on blasting effects of rock masses. Joints showed significant guidance effect on the propagation of cracks in blasting: promoting propagation of main vertical cracks deflecting to the ends of joints. Originality/value: The research results are expected to provide some theoretical bases in practical application of engineering blasting.